Level of enjoyment basketball Lessons Amongst Student of Physical Education and Sports sciences in the Kurdistan Region – Iraq - Abdullah, Khaled Hussein (Sulaimani Journal for Humanities, 2023)
Designing and examining - building a measure of enjoyment in basketball among students of colleges of physical education and sports sciences in the universities (KOYA, SALAHADDIN, SULAIMANI, and DUHOK) and identifying differences in enjoyment levels among students of colleges of physical education and sports sciences in the universities as mentioned earlier. The build sample consists of physical education students at (KOYA, SALAHADDIN, SULAIMANI, and DUHOK) universities for the academic year (2018-2019). The number of the sample was (550) students.The scale was applied to the sample. lecture Halls : lectures halls in universities ((Koya, Salahaddin, Sulaimani and Duhok) The researcher uses the descriptive method appropriate to the nature of the study. The research population consists of students of physical education faculties for the academic year (2018-2019) whose number is (550) individuals, divided into two groups: The experimental experiment group consists of (125) students with a percentage of (%29) of the research population and the (425) remaining students (%71) who answered the scale of the enjoyment level of basketball lessons represent the research sample. Furthermore, the researcher utilizes the scale of the enjoyment level of basketball lessons and Statistical Package of Social Sciences (SPSS) to analyze the collected data using the following formula (mean, standard deviation, percentage, correlation coefficient (spearman), ANOVA, least significant differences and t-test for individual samples). The results show that the level of enjoyment in basketball lessons is generally average among physical education students. There are statistically significant differences among the universities included in the study, with the priority for the university of SULAIMANI. The researcher presented the following conclusions that , All universities were of the average level of enjoyment in the second and fourth stage of basketball classes.There are differences between universities in the second and fourth stage in enjoying a basketball lesson in Favor of the University of SALAHADDIN. The researcher recommended that Having enjoyment in practical lessons has an effective impact on teachers, and providing them with educational units.